Isolated superior mesenteric artery dissection and median arcuate ligament syndrome. (3rd January 2019) - Tsuchida, Tomoya; Komiyama, Atsushi; Saruya, Shinji; Matsuda, Takahide
Abstract : Our case underscores the importance of recognizing MALS not only as a cause of postprandial epigastric pain but a rare facilitating factor in the development of isolated SMA dissection.